A new model for hiding text in an image using logical connective - Siti Dhalila, Mohd Satar; Fatimah, Ghazali; Nazirah, Abd Hamid (Science and Engineering Research Support Society, 2015)
The objective of this study is to propose a new model for hiding text in an image. The proposed model use logical connective in propositional logic to calculate a new binary number of secret message. This model can produce a low computational complexity of steganography because of the simplicity of the proposed algorithm. Moreover, the using of simple operator but very efficient is expected to be able to hide high capacity of a secret message.